Professional personnel allocation and capacity building requirement in disease prevention and control institutions in Beijing during COVID-19 epidemic: a cross- sectional survey - A-yan MAO; Yu-jie YANG; Shuai DU (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To summarize the status of emergency response-related professional/technical personnel deployment and replenishment and capacity building requirement in municipal and district disease prevention and control institutions of Beijing during coronavirus disease 2019 (COVID-19) epidemic for providing evidences to the management of human resource for epidemic control in the institutions. MethodsUsing cluster and convenient sampling, we conducted an online survey among 1 127 professionals in one municipal center and 4 district centers for disease control and prevention (CDC) in Beijing with a self-designed questionnaire during April - May, 2021. Absolute quantity, constituent ratio, and Fisher's exact test were adopted in statistical analyses with Microsoft Excel 2010 and SPSS 22.0 software. ResultsOf the 1 086 respondents with valid replies, 1 032 reported the involvement in COVID-19) epidemic control work and the majority (61.74%) of the involved personnel were with the specialty of public health, followed by those (13.18%) with health inspection. For the personnel assigned to on-site survey and sampling during the epidemic period, 26.70% were routinely engaged in infectious disease prevention and control, 10.49% in occupation/radiation/environment health surveillance and assessment, and 7.56% in non communicable disease prevention and control; for the personnel assigned to viral specimen detection, 33.86% were routinely engaged in pathogenic microorganism and biological specimen detection, 17.72% in infectious disease prevention and control, and 13.39% in and physical and chemical detection; while for the personnel assigned to information monitoring, data analysis and management, 28.98% were routinely engaged in infectious disease prevention and control, 8.48% in administrative management and quality control, and 7.89% in the management on public health emergency response, respectively. Nearly a half of the respondents reported the requirement for the improvement in epidemic control-related data acquisition and analysis, with 46.22%, 49.54%, 48.43%, and 49.45% of the respondents indicating the requirement for ability improvement in large-scale database integration and analysis, complex mathematical model modeling, big data acquisition and analysis, and data mining. ConclusionIn Beijing city, the CDC's personnel involved in COVID-19 epidemic containment were mainly those with the specialty of public health and health inspection and the day-to-day work in departments on disease control and prevention. The improvement for data management/analysis and detection method development/application are among the items of professional capability building most frequently reported by the personnel.